Fundamentals of risk management for process industry engineers - Hassall, Maureen; Lant, Paul (Elsevier, 2023)
Fundamentals of Risk Management for Process Industry Engineers outlines foundational principles of human-centered, sociotechnical risk management, and how they can be applied to deliver real improvements in risk identification, understanding, analysis, control, communication, and governance. To maximize sustainable competitiveness requires the identification and optimization of the range of risks that can impact a business. Hence, understanding the foundational principles of sociotechnical risk management is required to design and execute effective risk identification, optimization, and management strategies.